Nursing care of 80 years-old patient with type 2 diabetes at home - Bogusława Ryś; Kamila Górna; Ewelina Bąk; Julia Kostka (Kazimierz Wielki University, 2024)
Type 2 diabetes is one of the diseases of civilization that affects older people relatively more often.  It is called the plague of the 21st century. As the body ages, insulin sensitivity decreases significantly, which often results in impaired insulin secretion in the body. Type 2 diabetes in the elderly is currently a major clinical problem. Improperly treated diabetes leads to many dysfunctions in the body, such as: diabetic nephropathy, coronary artery disease, and in some cases it may lead to atherosclerosis occlusive of the arteries of the lower limbs. The theoretical part of the work included information about type 2 diabetes. The practical part included a case report of an 80-year-old patient with type 2 diabetes.